2009
DOI: 10.1128/jcm.01196-08
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing Fasciitis Caused by Haemophilus influenzae Type b in an Elderly Patient

Abstract: Necrotizing fasciitis caused by Haemophilus influenzae type b is a rare infection of the skin and soft tissues. The only previously reported case involved a healthy infant. We report herein the case of an 81-year-old Japanese woman with diabetes mellitus who developed necrotizing fasciitis caused by H. influenzae type b. CASE REPORTAn 81-year-old Japanese woman presented to the outpatient dermatology department at Kyoto University Hospital with painful swelling of the left leg. She had a history of type II dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…In addition, low Hib circulation rates due to the vaccine's "herd effect" may account for reduced maintenance of natural anti-Hib immunity in nonvaccinated populations (14). Severe cases of invasive Hib disease affecting adults have been reported (6,40). As Hib continues to circulate in countries with high pediatric Hib vaccine coverage (31), the public health guidelines recommend adult vaccination for some high-risk groups (anatomical or functional asplenia, congenital antibody, or complement deficiency) (34).…”
mentioning
confidence: 99%
“…In addition, low Hib circulation rates due to the vaccine's "herd effect" may account for reduced maintenance of natural anti-Hib immunity in nonvaccinated populations (14). Severe cases of invasive Hib disease affecting adults have been reported (6,40). As Hib continues to circulate in countries with high pediatric Hib vaccine coverage (31), the public health guidelines recommend adult vaccination for some high-risk groups (anatomical or functional asplenia, congenital antibody, or complement deficiency) (34).…”
mentioning
confidence: 99%
“…Monomicrobial (type 2) necrotizing fasciitis occurs less commonly, and is most often caused by streptococci. There are only eight published accounts of monomicrobial necrotizing fasciitis due to H. influenzae (Table 1) in the literature (Chalmers, 2010;Collette et al, 1987;Lee & Ip, 2010;McLellan et al, 2008;Robinson et al, 2010;Saito et al, 2009;Stumvoll & Fritsche, 1997;Ugai et al, 2014). To the best of our knowledge, this is the first report of monomicrobial cervicofacial necrotizing fasciitis due to H. influenzae.…”
Section: Discussionmentioning
confidence: 83%
“…Other epidemiological reports have suggested that the shift has been predominantly towards non-typable strains (Agrawal & Murphy, 2011). Among the previously reported cases of necrotizing fasciitis secondary to H. influenzae, five were Hib (Chalmers, 2010;Collette et al, 1987;Lee & Ip, 2010;Saito et al, 2009;Ugai et al, 2014), one was Hie (Robinson et al, 2010), one was serotype f (Hif) (McLellan et al, 2008) and one was non-typable (Stumvoll & Fritsche, 1997).…”
Section: Discussionmentioning
confidence: 98%
“…In our review, there are only 10 cases of necrotizing fasciitis associated with H. influenzae reported in the literature, 7 of which occurred in adults (Table 1) (2,(5)(6)(7)(8)(9)(10)(11)(12)(13). Three cases were secondary to Hif infection, as occurred for our patient.…”
mentioning
confidence: 89%
“…However, despite a remote history of breast cancer, our patient was otherwise healthy and in excellent physical condition at the time of presentation. Also, in the review of the prior reported cases, at least four were found to have occurred in relatively healthy individuals (5,7,9,12). In one case of a previously healthy man, an IgG3 and mannose-lectin binding deficiency was later discovered, which was thought to have possibly been a predisposing factor (5).…”
mentioning
confidence: 99%